2013
DOI: 10.1111/petr.12156
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of PD‐1 expression on CD8 T cells in patients post‐renal transplant irrespective of chronic high EBV viral load

Abstract: Studies have identified solid organ transplant recipients who remain asymptomatic despite maintaining CHL. Factors which determine the CHL state remain poorly understood but are likely to involve immunological control of the viral infection. We monitored expression of PD-1, a marker of T-cell exhaustion and viral persistence, on CD8 T cells in patients who resolved EBV infection as determined by undetectable EBV DNA (REI) and CHL patients. PD-1 expression on CD8 T cells was increased in the first year post-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Similar changes are observed for T helper cells (CD4+) with skewing towards T follicular helper cells (CD4+, PD-1+) and away from the antiviral T-helper type-1 (T-bet+) subset in persistent viral infection in mice [92]. This functional profile was related to antigen load in HIV-1 infected humans [93] and Moran et al [94] found the level of PD-1 expression in cytotoxic T cells (CD8+) to be increased post-transplantation, independent of EBV viral load, suggesting that these changes in the T cell population are at least partially caused by non-viral factors. The relative weight of chronic antigen stimulation in the process of T cell exhaustion remains however artificial since EBV on itself also induces IL-10 and TGFβ which in turn cause T cell exhaustion [88].…”
Section: Impact Of Chronic Antigen Stimulation On Microenvironmentsupporting
confidence: 62%
“…Similar changes are observed for T helper cells (CD4+) with skewing towards T follicular helper cells (CD4+, PD-1+) and away from the antiviral T-helper type-1 (T-bet+) subset in persistent viral infection in mice [92]. This functional profile was related to antigen load in HIV-1 infected humans [93] and Moran et al [94] found the level of PD-1 expression in cytotoxic T cells (CD8+) to be increased post-transplantation, independent of EBV viral load, suggesting that these changes in the T cell population are at least partially caused by non-viral factors. The relative weight of chronic antigen stimulation in the process of T cell exhaustion remains however artificial since EBV on itself also induces IL-10 and TGFβ which in turn cause T cell exhaustion [88].…”
Section: Impact Of Chronic Antigen Stimulation On Microenvironmentsupporting
confidence: 62%
“…Immunosuppression diminishes the quantity and quality of T cells, rendering them unable to produce cytokines essential for immune destruction, to include interferon‐gamma, interleukin 2 and tumour necrosis factor‐alpha (Wilsdorf et al , ). Chronic, persistent EBV antigenaemia can lead to upregulation of co‐inhibitory receptors such as PD‐1 (also termed PDCD1) on T lymphocytes, producing an exhausted phenotype of anti‐EBV T cells (Moran et al , ). EBV latency proteins, such as latent‐membrane protein (LMP), can activate the JAK/STAT pathway within infected B cells resulting in upregulation of PD‐L1 (also termed CD274), which can produce EBV‐specific T cell anergy when bound to its PD‐1 receptor (Ferreiro et al , ).…”
Section: Pathogenesismentioning
confidence: 99%
“…In line with this finding, Jones et al (17) also reported that the frequencies of EBNA1-and BZLF1-specific CD4 + interferon gamma (IFNγ)-producing T cells were decreased in PTLD patients compared to healthy individuals. Another study reported increased PD-1 expression on CD8 + T cells in transplant recipients with EBV infection suggesting T cell exhaustion (18), although PD-1 + CD8 + T cells retained protective functions in humanized mice infected with EBV (19).…”
Section: Introductionmentioning
confidence: 98%